Patient experience with clinical pharmacist services in Travis County Federally Qualified Health Centers - Jennifer Shin; Leticia Moczygemba; Jamie C. Barner; Aida Garza; Sara Linedecker-Smith; Maaya Srinivasa (Centro de Investigaciones y Publicaciones Farmaceuticas, 2020)
Background: Positive patient experiences with care have been linked to improved health outcomes. Patient experience surveys can provide feedback about the level of patient-centered care provided by clinical pharmacists and information about how to improve services. Objectives: Study objectives are: 1) To describe patient experience with clinical pharmacist services in a federally qualified health center (FQHC). 2) To determine if demographic or health-related factors were associated with patient experience. Methods: This cross-sectional survey included adult patients who were English or Spanish speaking, and completed a clinical pharmacist visit in March or April 2018. Patient experience was evaluated, on a 5-point Likert scale (1 = strongly disagree to 5 = strongly agree), with 10 items using four domains: pharmacist-patient interaction information provision, support for self-care, and involvement in decision making. In addition, one item was used to rate the overall experience. Demographic and health-related variables were also collected. Eligible patients completed the survey after their clinical pharmacist visit. Descriptive and inferential statistics, as well as Cronbach's alpha for scale reliability, were employed. Results: Respondents (N=99) were 55.4 (SD=12.1) years and 53.1% were women. Overall, patients rated their experiences very high with the 10-item scale score of 4.8 (SD=0.4) out of 5 points and the overall experience rating of 4.9 (SD=0.4) out of 5 points. With the exception of race, there were no differences between patient experience and demographic and health-related variables. African Americans had significantly (p=0.0466) higher patient experience scores compared to Hispanics. Conclusions: Patients receiving care in a FQHC highly rated their experience with clinical pharmacists. This indicates that clinical pharmacists provided a high level of patient-centered care to a diverse group.